Using artificial intelligence to improve public health: a narrative review - Olawade, David B.; Wada, Ojima J.; David-Olawade, Aanuoluwapo Clement; Kunonga, Edward; Abaire, Olawale; Ling, Jonathan (Frontiers in Public Health, 2023)
Artificial intelligence (AI) is a rapidly evolving tool revolutionizing many aspects of healthcare. AI has been predominantly employed in medicine and healthcare administrationHowever, in public health, the widespread employment of AI only began recently, with the advent of COVID-19. This review examines the advances of AI in public health and the potential challenges that lie ahead. Some of the ways AI has aided public health delivery are via spatial modelling, risk prediction, misinformation control, public health surveillance, disease forecasting, pandemic/epidemic modelling, and health diagnosis. However, the implementation of AI in public health is not universal due to factors including limited infrastructure, lack of technical understanding, data paucity, and ethical/privacy issues.